ナンキョク リュツォ・ホルム ワン デ サイシュ シタ コア チュウ ノ セキエイ サリュウ ノ ヒョウメン ソシキ - 清水, 文健; シミズ, フミタケ; 森脇, 喜一; モリワキ, キイチ; 伊藤, 真人; イトウ, マヒト; Shimizu, Fumitake; Moriwaki, Kiichi; Ito, Mahito (1988)
P(論文) リュツォ・ホルム湾で採取された海底堆積物や, 氷山中のshear planeに含まれていた石英砂粒の表面組織を, 走査型電子顕微鏡で観察した。これらの堆積物は, 位置から判断して明らかに大陸氷床による氷河成堆積物であり, 氷河成と認められた砂粒の含有率は最低でも55%, 一般に65~80%の値を示した。ところがこれらの砂粒のなかには, 氷河成特有の表面組織を備えてはいるものの, 丸みを帯びた凸型の外形や, 風の影響を示す衝突痕と見られる凹みをもつものもあり, 砂漠地域の砂粒の表面組織とも酷似するものが含まれていることがわかった。したがって, 上記の堆積物は氷河の環境下だけではなく, 強風の卓越する環境下にもおかれていたものと判断した。また, 一部ではあるが, 波浪の影響と判断される表面組織も認められた。 Observation of the surface textures of quartz grains contained within glacial and glacio-marine sediments which were obtained from the Lutzow-Holm Bay area was made by the scanning electron microscopy. These quartz grains contain from 55 to 80 per cent glacial ones. Many quartz grains have not only glacial but also wind-shaped characteristics. These characteristics indicate that the sediments passed through both glacial and windy environments. A few quartz grains have many V-shaped pits on their surfaces. This fact shows that some of the sediments received wave action near shore. departmental bulletin paper